Plasma Immersion Ion Implantation Increases Adhesive Bond Strength of PEK and PEEK to Dental Composites and Enables Hydrolysis Resistance - William T Lewin; Hedi Verena Kruse; Eva Tomaskovic‐Crook; Mahdi Shahmoradi; Dale Howes; David R McKenzie (Macromolecular Materials and Engineering)
Abstract The additive manufacturing technology known as selective‐laser‐sintering is available for the poly‐aryl‐ether‐ketone (PAEK) family of high‐strength polymers, enabling the rapid production of personalized dental and mandibular reconstructions at or near the point‐of‐care. PAEK mandibular segmental replacements, bridges, and abutments are transitioning to clinical use. There remains a need for improved adhesion between PAEK polymers and dental adhesives including dental composite resin cements. Without surface modification, there is a weak bond to PAEK polymers, especially when the surface of the polymer is smooth. Plasma‐immersion‐ion‐implantation (PIII) is applied to demonstrate a significant increase in the bond strength between Polyether–ether–ketone (PEEK) and Poly–ether–ketone (PEK) polymers and a commonly used dental composite resin cement, for multiple levels of interface roughness. A validated predictive model for the bond strength as a function of surface roughness expressed as a surface area ratio is presented that demonstrates the relative effect of PIII and mechanical interlocking. The results show that the bond strength achieved using PIII is retained even when the primer step is omitted, an important advance as the primer has been associated with hydrolysis‐induced weakening. A long‐term water immersion test shows that the PIII‐assisted primer‐free bond retains its strength while all primer‐assisted bonds are weakened.